RELEVANSI KEUTAMAAN-KEUTAMAAN SANTO YOSEF MENURUT SURAT APOSTOLIK PATRIS CORDE BAGI KELUARGA KATOLIK DEWASA INI - Astuti, Ana Yulia; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2021)
The formulation of the problem of this study is what is the content of the Apostolic Letter Patris Corde?, and how relevant are the virtues of Saint Joseph according to the Apostolic Letter Patris Corde for Catholic families today?. The researcher uses a qualitative literature study method, carried out by tracing written sources in the Holy Bible, Church documents, books, theses, and journals as well as articles on the internet that are relevant to the research topic. This study concludes: The virtues of Saint Joseph according to the Apostolic Letter Patris Corde are 1) Joseph, the beloved father; 2) Joseph, the gentle and loving father; 3) Joseph, the obedient father; 4) Joseph, the accepting father; 5) Joseph, the creatively courageous father; 6) Joseph, the working father; 7) Joseph, the shadow father. The results of the study show that the virtues of Saint Joseph according to the Apostolic Letter Patris Corde are very relevant to the life of Catholic families today by always being faithful to one's partner, being open to one's offspring, providing an example to children, accepting one another unconditionally, having creative courage to face challenges and difficulties, always being honest, and working together with God, and children seeing God's love and goodness in their parents.